CREATION OF WEAR-RESISTANT COMPOSITES COATED ON THE BASIS OF POWDER-BASED SELF-FLOWING ALLOYS BY ELECTRO-CONTACT SINTERING - Lopata, Larisa; Kachynska, Iryna; Solovykh, Andriy; Katerinich, Stanislav (Problems of Friction and Wear, 2024)
The paper examines the process of increasing the functional properties of coatings made from powders of self-fluxing alloys by using the method of electric contact sintering. It has been shown that the adhesive strength of the coatings is high. with the base is ensured by the formation of a wide diffusion zone on the side of the base. There is no liquid phase at the coating-part boundary. This indicates that, unlike surfacing, during electrical contact sintering there is no overheating and no mixing zone of the coating material with the metal of the part. X-ray study of the phase composition of coatings shows that under optimal conditions of electric contact sintering, the carbides present in the original powder are mainly retained in the sintered layer, which indicates the preservation of the hereditary properties of the coating material during electric contact sintering. The effect of grinding the carbide phase makes it possible to obtain sintered layers with evenly distributed carbide inclusions, which helps to increase the wear resistance of coatings. Carbide particles have a specific acute-angled shape, which indicates the preservation of the original properties and structure of the coating material during electrical contact sintering. Impulse temperature-force influence in the process of coating formation during electric contact cauterization leads to the dispersion of solid phase particles, which helps to increase the microhardness and wear resistance of the obtained coatings by 2-3 times. The developed technology for obtaining coatings from self-fluxing alloy powders by electric contact sintering leads to a decrease in the cost of manufacturing and restoration of parts due to the replacement of alloy steel with low-carbon steel with coatings from SFP SFS while increasing the resource of parts by 3-5 times.